Factors Influencing Postoperative Inpatient Rehabilitation Requirement After Surgical Intervention for Isolated Hip Fracture: A Multicenter Study - Daniel J. Lynch; Andrew Romero; James P. McFadden; Peter Zeblisky; Huazhi Liu; Darwin Ang (Orthopaedic Surgery)
ABSTRACT Purpose Hip fractures in the elderly, especially those discharged to a rehab facility, have historically been associated with poor outcomes. There has yet to be identified which patients have a higher likelihood of a rehab discharge after isolated hip fracture fixation. The purpose of this study was to identify factors that predispose patients to require short or long‐term rehab after surgical intervention of traumatic, isolated hip fractures. Methods Patients undergoing operative management of hip fractures (n = 71,849) from 2017 to 2019 at institutions that submitted data to a nationwide database were analyzed retrospectively. Various factors were compared between patients discharged to inpatient rehab (n = 56,178) versus home (n = 15,671). Results The rehab discharge group was significantly older and predominantly female. This cohort had a longer average hospital stay, higher incidence of diabetes, congestive heart failure, chronic renal failure, history of cerebrovascular accident, functionally dependent health status, hypertension, chronic obstructive pulmonary disease, dementia, baseline anticoagulation therapy, and history of myocardial infarction. DVT during hospitalization was encountered more often in patients discharged to rehab. Patients with femoral neck fractures and those undergoing total hip arthroplasty were more often discharged home. Patients with intertrochanteric hip fractures and those undergoing fracture fixation were more often discharged to rehab. Conclusions Multiple risk factors associated with a significantly higher likelihood of a rehab discharge after isolated hip fracture surgery were identified. Early identification of these patients may provide an opportunity to optimize patients for home discharge and better outcomes. Level of Evidence Level III, Case‐Control Study.